Thermal frictional analysis of a novel vibrating cylindrical turbulator in double tube heat exchangers for engine cooling - Yinwei Wang; Saleem Jasim Abbas; Ramdevsinh Jhala; Ankur Kulshreshta; N. Beemkumar; Vikasdeep Singh Mann; Ibrahim Mahariq (Case Studies in Thermal Engineering)
This study focuses on enhancing the thermal efficiency of a double-tube heat exchanger used in cooling systems for large-scale internal combustion engines by incorporating a novel vibrating cylindrical turbulator. The experimental investigation examined inlet Reynolds numbers ranging from 1052 to 8430 and evaluated various turbulator configurations, including fixed close-ended, fixed open-ended, vibrating close-ended, and vibrating open-ended cylindrical turbulators. Additionally, the impact of turbulator length, varying from 10 to 30 cm, on thermal-frictional characteristics was analyzed. The optimal configuration was determined using the thermal enhancement factor (TEF). Results showed that close-ended cylindrical turbulators significantly outperformed the open-ended configurations in terms of heat transfer and TEF. Although the vibrating turbulator produced a higher pressure drop compared to the fixed turbulator, it achieved a much higher heat transfer rate and TEF, making it a viable option for heat exchangers. The study also found that increasing the turbulator length leads to increased heat transfer, TEF, and pressure drop. The maximum TEF was recorded with the vibrating close-ended cylindrical turbulator, where heat transfer and pressure drop were up to 385 % and 95 % greater than those of a plain tube heat exchanger, respectively, resulting in a perfect TEF value of 3.45.